(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article reveals criminal liability for kidnapping. All parts of Article 137 of the Criminal Code of the Republic of Uzbekistan are disclosed, namely: kidnapping of a minor; for selfish or other base motives; by prior conspiracy by a group of persons; repeatedly or a dangerous repeat offender. As well as kidnapping committed by a particularly dangerous repeat offender; causing serious consequences; committed for the purpose of removing human organs and (or) tissues.